Model Matematika Penjadwalan Obat Kemoterapi Kanker secara Optimal Menggunakan Non-dominated Sorting Genetic Algorithm-II (NSGA-II) - Ashilah Azmii, Yusyifa; Yulianti, Kartika; Sispiyati, Ririn (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2025)
In this study, a mathematical model for cancer chemotherapy drug scheduling was developed, which is the problem of scheduling drugs given to patients. The mathematical model developed has an objective function of reducing cancer cells while reducing toxicity in the patient's body, with constraints in the form of limits for the number of healthy cells, cancer cells, drug concentration, and patient toxicity. The influential and interrelated variables are arranged in a system of differential equations consisting of the number of healthy cells, number of cancer cells, drug dose, drug concentration, patient toxicity and drug effect, which describes the chemotherapy of non-specific cancer cell cycles. Optimal solution was obtain numerically using Runge-Kutta Method and Non-dominated Sorting Genetic Algorithm-II (NSGA-II). The results showed that this algorithm was able to produce a solution with an optimal dosing schedule every 8 days for 106 days with 14 drug doses. Doses ranged from 20.00 to 29.55 mg/m² with an average of 24.28 mg/m² and a standard deviation of 3.64 mg/m² so as to minimize the number of cancer cells and damage to healthy cells.